2019
DOI: 10.1186/s13063-019-3312-9
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physical activity among community groups of older women in socio-economically disadvantaged areas: randomised feasibility study

Abstract: Background Insufficient physical activity (PA) is a major public health issue. Whilst PA is an important contributor to disease prevention, engagement in PA decreases with age, particularly among women in socio-economically disadvantaged areas. Research using existing support networks to engage ‘hard to reach’ populations in PA interventions is sparse. We developed and tested the feasibility of a PA-promoting intervention for older women within existing community groups in socio-economically disad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 74 publications
(99 reference statements)
3
11
0
Order By: Relevance
“…14,15 Similar to NICE guidelines, 16 our findings highlight a need to recognise local context, social norms and community needs when designing and implementing health promotion initiatives and the importance of delivering services in familiar, inclusive community venues that match socio-cultural norms. The findings concur with previous evidence 17,18 that residents of certain areas were unlikely to attend some locations due to sociopolitical issues.…”
Section: What Is Already Known On This Topic?supporting
confidence: 91%
See 1 more Smart Citation
“…14,15 Similar to NICE guidelines, 16 our findings highlight a need to recognise local context, social norms and community needs when designing and implementing health promotion initiatives and the importance of delivering services in familiar, inclusive community venues that match socio-cultural norms. The findings concur with previous evidence 17,18 that residents of certain areas were unlikely to attend some locations due to sociopolitical issues.…”
Section: What Is Already Known On This Topic?supporting
confidence: 91%
“…Social familiarity, being with like-minded people and being comfortable in a setting has been found to be conducive to recruitment and intervention effectiveness. 17,38 Further, our findings indicate that health promotion services that involve women from their community in leadership may help overcome the reported low female participation rates in PA programmes. 39,40 This study reveals that whilst delivery of services in convenient locations tended to increase participation, 19,41 some residents prefer the anonymity of 'out of area' services, potentially due to the perceived stigma of attendance.…”
Section: What This Study Addsmentioning
confidence: 71%
“…In contrast, other researchers have reported that nancial constraints and low socioeconomic status are barriers to effective self-management [42,43]. The use of existing social support groups has been also underlined as an acceptable and attractive method of delivering a self-management intervention to older people in socio-economically disadvantaged areas [44]. The results obtained in health literacy are in line with those reported from similar group-based interventions [45].…”
Section: Discussionsupporting
confidence: 53%
“…In contrast, other researchers have reported that financial constraints and low socioeconomic status are barriers to effective self-management [ 43 , 44 ]. The use of existing social support groups has been also underlined as an acceptable and attractive method of delivering a self-management intervention to older people in socio-economically disadvantaged areas [ 45 ]. The results obtained in health literacy are in line with those reported from similar group-based interventions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%